Effect of soy protein supplementation on muscle adaptations, metabolic and antioxidant status, hormonal response, and exercise performance of active individuals and athletes: a systematic review of randomised controlled trials - Zare, R.; Devrim-Lanpir, A.; Guazzotti, S.; Redha, A. A.; Prokopidis, K.; Spadaccini, D.; Cione, E.; Henselmann, M.; Aragon, A. A. (Sports Medicine, 2023)
Background: Protein supplements are important to maintain optimum health and physical performance, particularly in athletes and active individuals to repair and rebuild their skeletal muscles and connective tissues. Soy protein (SP) has gained popularity in recent years as an alternative to animal proteins. Objectives: This systematic review evaluates the evidence from randomised controlled clinical trials of the effects of SP supplementation in active individuals and athletes in terms of muscle adaptations, metabolic and antioxidant status, hormonal response and exercise performance. It also explores the differences in SP supplementation effects in comparison to whey protein. Methods: A systematic search was conducted in PubMed, Embase and Web of Science, as well as a manual search in Google Scholar and EBSCO, on 27 June 2023. Randomised controlled trials that evaluated the applications of SPs supplementation on sports and athletic-related outcomes that are linked with exercise performance, adaptations and biomarkers in athletes and physically active adolescents and young adults (14 to 39 years old) were included, otherwise, studies were excluded. The risk of bias was assessed according to Cochrane`s revised risk of bias tool. Results: A total of 19 eligible original research articles were included that investigated the effect of SP supplementation on muscle adaptations (n = 9), metabolic and antioxidant status (n = 6), hormonal response (n = 6) and exercise performance (n = 6). Some studies investigated more than one effect. SP was found to provide identical increases in lean mass compared to whey in some studies. SP consumption promoted the reduction of exercise-induced metabolic/blood circulating biomarkers such as triglycerides, uric acid and lactate. Better antioxidant capacity against oxidative stress has been seen with respect to whey protein in long-term studies. Some studies reported testosterone and cortisol fluctuations related to SP; however, more research is required. All studies on SP and endurance performance suggested the potential beneficial effects of SP supplementation (10-53.3 g) on exercise performance by improving high-intensity and high-speed running performance, enhancing maximal cardiac output, delaying fatigue and improving isometric muscle strength, improving endurance in recreational cyclists, increasing running velocity and decreasing accumulated lactate levels; however, studies determining the efficacy of soy protein on VO2max provided conflicted results. Conclusion: It is possible to recommend SP to athletes and active individuals in place of conventional protein supplements by assessing their dosage and effectiveness in relation to different types of training. SP may enhance lean mass compared with other protein sources, enhance the antioxidant status, and reduce oxidative stress. SP supplementation had an inconsistent effect on testosterone and cortisol levels. SP supplementation may be beneficial, especially after muscle damage, high-intensity/high-speed or repeated bouts of strenuous exercise.